2023
DOI: 10.1093/sxmrev/qead015
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal self-lubrication following peritoneal, penile inversion, and colonic gender-affirming vaginoplasty: a physiologic, anatomic, and histologic review

Abstract: Introduction Vaginal self-lubrication is central to the sexual satisfaction and healthy genitourinary function of patients who have undergone gender-affirming vaginoplasty (GAV). Secretory capacities of different neovaginal lining tissues have been variably described in the literature, with little evidence-based consensus on their success in providing a functionally self-lubricating neovagina. We review the existing neovaginal lubrication data and the anatomy, histology, and physiology of pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Additionally, the risk of reatresia exists when the wound is not covered with appropriate materials after cervicoplasty and vaginoplasty ( 21 ). Currently, the commonly used materials for covering the vagina include the amniotic membrane, a small intestinal submucosa graft, skin, biological materials, peritoneum, and other flaps ( 19 , 21 - 25 ). However, most papers on the application of these materials have been case reports, and all of these materials (except the skin and the peritoneum) require the application of allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the risk of reatresia exists when the wound is not covered with appropriate materials after cervicoplasty and vaginoplasty ( 21 ). Currently, the commonly used materials for covering the vagina include the amniotic membrane, a small intestinal submucosa graft, skin, biological materials, peritoneum, and other flaps ( 19 , 21 - 25 ). However, most papers on the application of these materials have been case reports, and all of these materials (except the skin and the peritoneum) require the application of allografts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, most neovaginal canals are noted to be moist at baseline. A recent review demonstrated that neither penoscrotal skin, bowel, nor peritoneumlined neovaginas provided functional lubrication comparable to a natal vagina, thus concluding that existing evidence does not support choosing one type of neovaginal lining based on lubrication outcomes alone [25].…”
Section: Skinmentioning
confidence: 99%
“…Histologically, each layer is composed of three sublayers: the mesothelium, basal lamina, and submesothelial stroma. The mesothelium is made up of simple squamous cells that house lamellar bodies, which produce lipid-containing secretions for lubrication [25,26].…”
Section: Peritoneummentioning
confidence: 99%
See 1 more Smart Citation
“…It includes a bilateral orchidectomy, penectomy, clitoroplasty, labioplasty, and vaginoplasty. Penile inversion vaginoplasty still presents the gold Life 2023, 13, 2212 2 of 14 standard technique, while intestinal and peritoneal pull-through vaginoplasties are usually reserved for re-do cases and cases with insufficient penile skin [10][11][12][13]. The new female genitalia are created from the penile and scrotal skin, a piece of the glans with neurovascular elements, and the proximal part of the urethra.…”
Section: Introductionmentioning
confidence: 99%